BARRIERS AGAINST IMPLEMENTING AND MANAGING QUALITY IN INFORMATION TECHNOLOGY INDUSTRY OF PAKISTAN - Ahsan, Ali (The Nucleus, 2010)
This research paper presents major barriers to implement quality in IT sector of Pakistan. The paper not only explores (exploration w.r.t quality management covering discussion like what is done, what is not done, what are the loopholes, what must be done and / or what must not be done), but also presents detailed explanation of the main highlights by performing necessary qualitative analysis. In addition to exploration and explanation of barriers (the paper specifically talks of barriers concerning behavior, management and culture) to quality within IT sector of Pakistan, the paper also explains all the important issues arising due to the deprived quality management. As a result of detailed analysis performed, the paper finally identifies important remedies for revitalization of quality management function as recommendations. Mainly, exploration, explanation and analysis of reasons and remedial actions are focused. Discussion and analysis is limited to behavioral, cultural and managerial perspective.